Diagnostik und Therapie der Nephrolithiasis - Pfau, A.; Eckardt, Kai-Uwe; Knauf, F. (Internist, 2015)
Kidney stones are a common and increasing problem worldwide. Nephrolithiasis is frequently a chronic disease given the risk of recurrence following passage of a first stone.In the present article, an update on the diagnosis and treatment of kidney stones relevant for internal medicine physicians is provided.This review is based on a selective literature search and our own work.The diagnosis of kidney stones is based on the clinical history and physical examination. Confirmatory radiologic tests include noncontrast computerized tomography or ultrasonography with both techniques having recently been shown to have equivalent overall outcomes. The therapy of kidney stones is based on the clinical presentation and diagnostic findings (e.g., fever, response to pain management, and demonstration of relevant obstruction) as well as location, size, and composition of the stone. If invasive treatment is being considered, the urology department should be consulted. Given the high risk of recurrence, stone analysis must be performed as well as the concentration of lithogenic and litholytic substances measured in a 24-h urine collection. The newly established recurrence of kidney stone nomogram (ROKS nomogram) identifies kidney stone formers at greatest risk for a second symptomatic episode who may benefit from medical intervention.
EVALuna2:3792